Pembangunan Sistem Knowledge Repository Manajemen Penyuluhan Pertanian dalam Rangka Mendukung Revitalisasi Penyuluhan Pertanian: Help Desk Penyuluhan Pertanian Komoditas Tanaman Pangan - Harisno, Harisno; Jingga, Freddy (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Development of knowledge Repository Management System for Agricultural Extension aims to help the extension worker function for at least in three things: technology transfer, facilitation and advisory to farmers as the main actors of agribusiness. To support these functions, the extension workers need to master as well as utilize information and communication technology. A help Desk of Agricultural Extension System is developed using PC with PHP programming language. Data management in the Database of Agricultural Extension Knowledge Repository is managed by using MySQL. The web-based application will enable users to access data, information and agricultural extension knowledge based on needs. Help Desk of Agricultural Extension System is a knowledge repository that can be used to help the agricultural extension in disseminating agricultural technology packages from the on-farm upstream to the downstream sub-system, and can be used as a medium of communication forums about problems of actual agricultural practices.